Asesmen Bimbingan Rohani Islam sebagai Motivasi Hidup pada Pasien Kanker di Rumah Singgah Dompet Dhuafa Purwokerto - Delapanca, Gusmi Adam; Islamy, Fawwaz Adzansyah (Da'wah Faculty of UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Abstract: The Sehati Patient Shelter Home is a facility that provides housing and health services for cancer patients who come from outside the city and cannot afford it. This research aims to explore the role of spiritual guidance as life motivation for cancer patients at the Sehati Dompet Dhuafa Patient Shelter Home, Purwokerto. This research uses a qualitative descriptive approach with data collection techniques through interviews with employees, including two people named Mrs. Titi and Maulana, supported by direct observation at the halfway house. The data obtained is then subjected to data analysis and discussion. The results of the research show that spiritual guidance is given to cancer patients who are undergoing treatment so that they can help them face life's challenges in dealing with cancer in accordance with the teachings of Islam. Islamic spiritual guidance services provide motivation, calm, and patience to patients, as well as provide understanding to the patient's family so that they always provide support in the healing process of cancer patients. The role of clergy as facilitators is important in guiding, caring for, and improving the spiritual quality of Islam holistically. Abstrak: The Sehati Patient Shelter Home is a facility that provides housing and health services for cancer patients who come from outside the city and cannot afford it. This research aims to explore the role of spiritual guidance as life motivation for cancer patients at the Sehati Dompet Dhuafa Patient Shelter Home, Purwokerto. This research uses a qualitative descriptive approach with data collection techniques through interviews with employees, including two people named Mrs. Titi and Maulana, supported by direct observation at the halfway house. The data obtained is then subjected to data analysis and discussion. The results of the research show that spiritual guidance is given to cancer patients who are undergoing treatment so that they can help treat cancer in accordance with the teachings of Islam. Islamic spiritual guidance services provide motivation and patience to patients, as well as provide understanding to the patient's family so that they always provide support in the cancer patient's healing process. The role of clergy as facilitators is important in guiding, caring for, and improving the spiritual quality of Islam holistically.